Criminal defendants' family and the death penalty in China - a case analysis. Issue 2 (3rd May 2020) - Lu, Hong; Li, Yudu; Liang, Bin
ABSTRACT: The restorative justice movement has increased the rights of consciousness for crime victims and their families globally. Though the practice of family group conferences in Australia and New Zealand and the court-ordered mediation programmes in China have increasingly involved defendants and their families, their roles in the criminal justice system have not been the main focus of academic inquiries. Citing a high-profile capital case in China, the Nian Bin case, this study examines the defendant family's strategies in seeking legal redress, managing physical, emotional and financial tolls as well as coping with the victim families, throughout their eight-year pursuit of Nian's exoneration. Given Confucian teachings on the importance of family to the individual and the society at large, this study provides a microscopic view into various precipitating factors for a capital defendant's family activism. It also draws broader implications for China's criminal justice reforms and the restorative justice movement.